Editorial Board Thoughts: Requiring and Demonstrating Technical Skills for Library Employment - Morton-Owens, Emily (Information Technology and Libraries, 2016)
Editorial Board Thoughts: Requiring and Demonstrating Technical Skills for Library Employment